Ultrasound-Enhanced Bioscouring of Greige Cotton: Regression Analysis of Process Factors. Issue 1 (January 2015) - Easson, Michael W.; Wojkowski, Stefan; Condon, Brian; Yeater, Kathleen; Slopek, Ryan; Fortier, Chanel
Ultrasound-enhanced bioscouring process factors for greige cotton fabric are examined with custom experimental design using statistical principles. Optimal bioscouring conditions are determined for enzyme concentration, process time, ultrasonic power, and frequency. An equation is presented which predicts bioscouring performance based upon percent reflectance values obtained from UV-Vis measurements of ruthenium red stained fabrics. Significant material and engineering cost savings can be achieved through the adoption of optimized factors.